Mutations in the Katnb1 gene cause left–right asymmetry and heart defects. Issue 12 (5th September 2017) - Furtado, Milena B.; Merriner, D. Jo; Berger, Silke; Rhodes, Danielle; Jamsai, Duangporn; O'Bryan, Moira K.
Abstract : Background : The microtubule‐severing protein complex katanin is composed two subunits, the ATPase subunit, KATNA1, and the noncatalytic regulatory subunit, KATNB1. Recently, the Katnb1 gene has been linked to infertility, regulation of centriole and cilia formation in fish and mammals, as well as neocortical brain development. KATNB1 protein is expressed in germ cells in humans and mouse, mitotic/meiotic spindles and cilia, although the full expression pattern of the Katnb1 gene has not been described.Results: Using a knockin‐knockout mouse model of Katnb1 dysfunction we demonstrate that Katnb1 is ubiquitously expressed during embryonic development, although a stronger expression is seen in the crown cells of the gastrulation organizer, the murine node. Furthermore, null and hypomorphic Katnb1 gene mutations show a novel correlation between Katnb1 dysregulation and the development of impaired left–right signaling, including cardiac malformations.Conclusions: Katanin function is a critical regulator of heart development in mice. These findings are potentially relevant to human cardiac development. Developmental Dynamics 246:1027–1035, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: The katanin p80 regulatory subunit is required for the appropriate looping of the embryonic heart. Abnormal KATNB1 function lead to defective left‐right heart looping and the abnormal positioning of vessels.